A General Strategy for Efficiently Constructing Multifunctional Cluster Fillers Using a Three-Fluid Nozzle Spray Drying Technique for Dental Restoration. (January 2022) - Yang, Dan-Lei; Wang, Dan; Niu, Hao; Wang, Rui-Li; Liu, Mei; Zhang, Fei-Min; Wang, Jie-Xin; Zhu, Mei-Fang
Abstract: Multifunctional fillers are greatly required for dental resin composites (DRCs). In this work, a spray dryer with a three-fluid nozzle was applied for the first time to construct high-performance complex nanoparticle clusters (CNCs) consisting of different functional nanofillers for dental restoration. The application of a three-fluid nozzle can effectively avoid the aggregation of different nanoparticles with opposite zeta potentials before the spray drying process in order to construct regularly shaped CNCs. For a SiO2 –ZrO2 binary system, the SiO2 –ZrO2 CNCs constructed using a three-fluid nozzle maintained their excellent mechanical properties ((133.3 ± 4.7) MPa, (8.8 ± 0.5) GPa, (371.1 ± 13.3) MPa, and (64.5 ± 0.7) HV for flexural strength, flexural modulus, compressive strength, and hardness of DRCs, respectively), despite the introduction of ZrO2 nanoparticles, whereas their counterparts constructed using a two-fluid nozzle showed significantly decreased mechanical properties. Furthermore, heat treatment of the SiO2 –ZrO2 CNCs significantly improved the mechanical properties and radiopacity of the DRCs. The DRCs containing over 10% mass fraction ZrO2 nanoparticles can meet the requirement for radiopaque fillers. More importantly, this method can be expanded to ternary or quaternary systems. DRCs filled with SiO2 –ZrO2 –ZnO CNCs with a ratio of 56:10:4 displayed high antibacterial activity (antibacterial ratio > 99%) in addition to excellent mechanical properties and radiopacity. Thus, the three-fluid nozzle spray drying technique holds great potential for the efficient construction of multifunctional cluster fillers for DRCs.